Interpreting Competitive Advantage : Evidence from Existing Literature - Prasad, S. Shyam (Indian Journal of Marketing, 2020)
The importance of competitive advantage cannot be overemphasized. Every firm strives to gain some advantage in the market that they operate. A vast amount of research has gone into the different aspects of competitive advantage, and yet, a universally accepted definition has not emerged to date. Definitions that have appeared are few and far between. Only one paper focused on its measurement, though the author did not find any instance of it having been used in the industry or academia. Therefore, the objective of this paper was to collate different perspectives of competitive advantage existing in the extant literature and present the current understanding of the term. The papers published in the last two decades have been taken into consideration. This article has been written carefully by selecting leading literature on competitive advantage from databases such as Google Scholar, Proquest, JSTOR, and miscellaneous sources. Also, a workable definition of competitive advantage was included in the discussion section, fulfilling the gap. This study is unique in the sense that it tries to fulfil the lonazag-felt need for a formal, simple, and easy to interpret definition of competitive advantage.